Exploring farmers' understanding of and responses to endemic animal health and welfare issues in the UK. (23rd September 2021) - Mahon, Niamh; Clark, Beth; Proctor, Amy; Holloway, Lewis
Abstract: Background: This paper uses two endemic health conditions to explore farmer understandings of and responses to livestock health and welfare issues. Methods: The findings are based on a survey of 42 livestock farmers in the north of England, exploring how they manage lameness in sheep and cattle and bovine viral diarrhoea in cattle. We identify similarities and differences in their approaches. Results: Two themes emerge. (1) The importance of difference between animal types (i.e., beef cattle, dairy cattle and sheep), which highlights the 'complex' and 'multifactorial' nature of animal health and welfare. It is necessary to unpack this to understand the interplay of animal, resource and management issues in farmer responses. (2) Previous research has identified 'lack of knowledge' as a key welfare issue. Our findings reveal farmers are in fact seeking, acquiring and sharing knowledge on practices related to the management of animal health however individual circumstance and context influence how this translates in practice. Conclusion: Our research highlights the importance of integrating different perspectives and knowledges as a way of understanding and responding to animal health and welfare concerns. Facilitating knowledge exchange both within and between different groups and sectors is vital in achieving this.